Lacustrine systems of Clearwater Mesa (James Ross Island, north-eastern Antarctic Peninsula): Geomorphological setting and limnological characterization - Roman, Matej; Nedbalová, Linda; Kohler, Tyler J.; Lirio, Juan Manuel; Coria, Silvia Herminda; Kopácek, Jirí; Vignoni, Paula A.; Kopalová, Katerina; Lecomte, Karina Leticia; Elster, Josef; Nývlt, Daniel (Antarctic Science)
Lentic freshwater habitats are important centres of biodiversity within the infrequent ice-free oases across Antarctica. Given imminent climate changes, it is crucial to catalogue these habitats in order to provide baseline data for future monitoring and biological surveys. The lacustrine systems of Clearwater Mesa, a previously unexplored part of James Ross Island, north-eastern Antarctic Peninsula, are described here. We conducted basic geomorphological and limnological surveys over three Antarctic summers (2009-16) to characterize landscape evolution, infer the origin of lake basins and assess the variability in their water chemistry. Stable shallow lakes, formed in depressions between lava tumuli following the last deglaciation, were found to dominate the volcanic mesa, although several peripheral lakes in ice-proximal settings appear to have formed recently as a result of post-Neoglacial ice recession. We found large heterogeneity in conductivity (~10-7000 μS cm-1), despite the lithologically uniform substrate. This variability was shown to be related to lake type, basin type (open vs closed), meltwater source and proximity to the coast. Inter-annual differences were attributed to changes in sea spray influx and snow accumulation driven by variable weather conditions. Overall, the ion composition of lakes suggested that sea spray was the dominant source of ions, followed by the weathering of bedrock. Fil: Roman, Matej. Charles University; República Checa. Masaryk University; República Checa Fil: Nedbalová, Linda. Charles University; República Checa Fil: Kohler, Tyler J. Charles University; República Checa Fil: Lirio, Juan Manuel. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Coria, Silvia Herminda. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Kopácek, Jirí. Institute Of Hydrobiology, Biology Centre Of ...